Ketepatan Penanganan Keluhan Terhadap Customer Value Creation Pada Pasien BPJS di RS X - Theresia Marditama; Nur Pudyastuti Pratiwi; Artarina D.A Samoedra; Harun Heri Trismiyanto; Arief Prayitno; Sani Fitriyani; Rika Nur Latifah; Mesya Aura Lova; Della Purnama Sari (Jurnal Ners, 2026)
Patient satisfaction is a major indicator of the quality of health services. One important factor that influences satisfaction is the responsiveness of the hospital to patient complaints. Effective complaint handling can increase trust, improve service reputation, and contribute to continuous quality improvement. The purpose of this study was to determine the accuracy of complaint handling in increasing customer value creation at X Hospital. The research method in this study was descriptive verification using a questionnaire. The sample method studied was using the purposive sampling method. Data analysis used simple linear regression and correlation. The results showed that there was a positive and significant influence between complaint handling and customer value creation. Keywords: Patient Satisfaction, Service Quality, Complaint Handling, Customer Value Creation